A systematic review and meta‐analysis of treatments for rapid cycling bipolar disorder. (20th July 2022) - Strawbridge, Rebecca; Kurana, Suman; Kerr‐Gaffney, Jess; Jauhar, Sameer; Kaufman, Kenneth R.; Yalin, Nefize; Young, Allan H.
Abstract: Objectives: Rapid cycling is a common and disabling phenomenon in individuals with bipolar disorders. In the absence of a recent literature examination, this systematic review and meta‐analysis aimed to synthesise the evidence of efficacy, acceptability and tolerability of treatments for individuals with rapid cycling bipolar disorder (RCBD). Method: A systematic search was conducted to identify randomised controlled trials assigning participants with RCBD to pharmacological and/or non‐pharmacological interventions. Study inclusion and data extraction were undertaken by two reviewers independently. The primary outcome was continuous within‐subject RCBD illness severity before and after treatment. Pre‐post random effects meta‐analyses were conducted for each outcome/intervention arm studied, generating a standardised effect size (hedge's g ) and 95% confidence interval (CI). Results: A total of 34 articles describing 30 studies were included. A total of 16 separate pharmacological treatments were examined in contrast to 1 psychological therapy study. Only quetiapine and lamotrigine were assessed in >5 studies. By assessing 95% CI overlap of within‐subject efficacy effects compared to placebo, the only interventions suggesting significant depression benefits (placebo g = 0.60) were olanzapine (with/without fluoxetine; g = 1.01), citalopram ( g = 1.10) and venlafaxine ( g = 2.48). For mania, benefits were indicated for quetiapine ( g = 1.01), olanzapine ( g = 1.19) and aripiprazole ( g = 1.09), versus placebo ( g = 0.33). Most of these effect sizes were from only one trial per treatment. Heterogeneity between studies was variable, and 20% were rated to have a high risk of bias. Conclusions: While many interventions appeared efficacious, there was a lack of robust evidence for most treatments. Given the limited and heterogeneous evidence base, the optimal treatment strategies for people with RCBD are yet to be established.